Correlation between Urinary Angiotensin Converting Enzyme-2 & Micro Albuminuria in Non-Diabetic-Hypertensive and Type 2 Diabetic-Hypertensive patients - Mah-E-Jabeen Sear, Saima Mukhtar, Iram Qamar, Shaista Hussain, Sara Naeem, Hafeesa Naz, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The Renin Angiotensin System (RAS) is one of the main contributors to insulin resistance which leads to T2DM and its complications. The ACE2/Angiotensin-(1-7)/Mas axis has lately been anticipated to function as a negative regulator of the RAS, consequently, rendering a shielding task against progress of type 2 diabetes, as well as, lowering blood pressure. Aim: To correlate urinary angiotensin 2 levels and microalbuminuria in Type 2 Diabetic and non-Diabetic-hypertensive patients. Methods: A particular population of selected subjects was categorized into 2 groups, with 49 subjects in each group. Diabetic and hypertensive patients were selected from the SIMS diabetic Clinic and medical wards, Lahore. Anthrometric parameters, as well as, BSR were recorded in the clinics. Blood and urine samples were collected and stored for evaluating the biochemical parameters in the Physiology Laboratory, UHS. Results: Microalbuminuria, as well as urinary ACE2 levels in group A (non-diabetic-hypertensive subjects), were greater than in group B (diabetic-hypertensive subjects). There was a significant positive correlation between uACE2 levels and microalbuminuria in group A patients. Conclusion: Although the current study reinforced the fact that both T2DM and hypertension are risk factors for CKD, contrary to our prediction based on evidence gained from various research studies, we were unable to prove that urinary ACE 2 levels are higher in patients with hypertension compounded with diabetes mellitus.